Changes in plant function and root mycobiome caused by flood and drought in a riparian tree. (16th March 2020) - Martínez-Arias, Clara; Sobrino-Plata, Juan; Macaya-Sanz, David; Aguirre, Natalie Marie; Collada, Carmen; Gil, Luis; Martín, Juan Antonio; Rodríguez-Calcerrada, Jesús
Abstract: Under increasingly harsh climatic conditions, conservation of threatened species requires integrative studies to understand stress tolerance. Riparian Ulmus minor Mill. populations have been massively reduced by Dutch Elm disease (DED). However, resistant genotypes were selected to restore lost populations. To understand the acclimation mechanisms to the succession of abiotic stresses, ramets of five DED-tolerant U. minor genotypes were subjected to flood and subsequently to drought. Physiological and biochemical responses were evaluated together with shifts in root-fungal assemblages. During both stresses, plants exhibited a decline in leaf net photosynthesis and an increase in percentage loss of stem hydraulic conductivity and in leaf and root proline content. Stomatal closure was produced by chemical signals during flood and hydraulic signals during drought. Despite broad similarities in plant response to both stresses, root-mycobiome shifts were markedly different. The five genotypes were similarly tolerant to moderate drought, however, flood tolerance varied between genotypes. In general, flood did not enhance drought susceptibility due to fast flood recovery, nevertheless, different responses to drought after flood were observed between genotypes. Associations were found between some fungal taxonomic groups and plant functional traits varying with flood and drought (e.g. proline, chlorophyll and starch content) indicating that the thriving of certain taxa depends on host responses to abiotic stress.